Revival of Chinese Nationalism in the 90s (Czech Journal of International Relations, 2000)
Yongnian Zheng: Discovering Chinese Nationalism in China: Modernization, Identity and international Relations. 1st ed. Cambridge (United Kingdom): Cambridge University Press, 1999, 189 stran, ISBN 0-521-64180-2.Jonathau Unger (ed.): Chinese Nationalism (autoři 9 esejů: James Townsend, Prasenjit Duara, John Fitzgerald, Lucian W. Pye, Wang Gungwu, Allen Chum, George T. Crane, Edward Friedman, Geremie R. Barmé). Contemporaty China Papers. 1st ed. New York: Australian National University, 1996, 218 stran, ISBN 1-56324-802-6.